Ensuring food security as a field of activity of executive authorities - Averianova, Natalia Nikolaevna; Alekseeva, Marina V. (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
Introduction. Ensuring food security is an important task of any modern state. Meanwhile, this task is complex and, therefore, is being implemented in a number of directions. Based on this, a number of public authorities have separate powers in this area, among which federal executive authorities play a special role. In this regard, the issue of forming an administrative and legal mechanism for ensuring food security and determining its legal nature in this context is becoming relevant. Theoretical analysis. The conceptual provisions of legal acts on the activities of federal executive authorities in the field of food security have been analyzed, and the main directions of their activities in this area have been identified. Empirical analysis. Based on a systematic approach, the authors draw conclusions on the legal nature of the powers of federal executive authorities in the field of food security. Results. It has been revealed that food security in the context of the functioning of the administrative and legal mechanism for its ensuring can be considered as a national goal, a strategic task of an integrated nature; its implementation is directed by the relevant powers of federal executive authorities, which correlate with their main functions established by the specified regulatory legal acts.